2018
DOI: 10.3390/su10061877
|View full text |Cite
|
Sign up to set email alerts
|

Differences of Corporate Environmental Responsibility in Small and Medium Enterprises: Spain and Norway

Abstract: Abstract:The purpose of this paper is to analyze the factors that are related to Small and Medium Enterprises' (SMEs') environmental attitude. We focus on Spain and Norway-two contrasting countries in this regard. Drawing on evidence from the Flash Eurobarometer 381 Survey: SMEs, Resource Efficiency and Green Markets, the results show that there is a significant difference on environmental commitment in favor of Norway. Our estimation results show that firms' structural characteristics are strong factors influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 24 publications
(39 reference statements)
3
15
0
Order By: Relevance
“…It is worth mentioning that company E15, with its short time of existence (only seven years), already stands out in the sustainability aspect. It also reinforces the finding in the study of [22], describing that in Spain, the newer companies showed greater willingness to go beyond environmental legislation.…”
Section: Findings and Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…It is worth mentioning that company E15, with its short time of existence (only seven years), already stands out in the sustainability aspect. It also reinforces the finding in the study of [22], describing that in Spain, the newer companies showed greater willingness to go beyond environmental legislation.…”
Section: Findings and Resultssupporting
confidence: 87%
“…It is worth mentioning that company E15, with its short time of existence (only seven years), already stands out in the sustainability aspect. It also reinforces the finding in the study of [22], describing that in Spain, the newer companies showed greater willingness to go beyond environmental legislation. No companies scored between 51 and 60 points, which would indicate agreement with regard to emerging issues of management and the use of corporate social responsibility to achieve its objectives.…”
Section: Findings and Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Therefore, the aim of this study is to address this gap and provide further insights through empirical analysis of the outcomes of implementing the concept of sustainability in SMEs. To achieve the aforementioned, CSR is taken as a reference, as recently noted by authors such as Aguado and Holl [7] or Schmidt et al [2], as it considers the main concepts and strategies of firms to integrate environmental concerns in their business operations and activities.…”
Section: Introductionmentioning
confidence: 99%